PEMEKARAN DESA DAN IMPLIKASINYA TERHADAP KEHIDUPAN MASYARAKAT - Meli Lutpiah; Suryadi Suryadi; Fuad Faizi (UIN Siber Syekh Nurjati Cirebon, 2017)
ABSTRACTÂ Village Desa Kramat Jaya is a result of the division which was originally a part of the village Werasari. Expansion of the village is one of the steps the government in the distribution of development in an effort to improve the welfare of society through a policy of regional expansion. This research method is descriptive qualitative method with data collection through interviews, observation, documentation and literature. The results of his research is the process of expansion Desa Kramat Jaya stems from government policies as a driver of the expansion, public aspirations at the hamlet, village expansion plan study Kramat Jaya at the village level, the submission to the expansion of local government, and the inauguration of Desa Kramat Jaya. The division has implications for the lives of the people in the village of Kramat Jaya, such as government reform Desa Kramat Jaya, the impact of the reallocation of village on the lives of farmers through the establishment of Farmers Group Association (Gapoktan), and increased welfare through the development of infrastructure such as, village offices, village health post (Poskesdes), rural roads, rural feeder roads, retaining walls (TPT) or irrigation channels, and kiosks. Â Keyword: process, the implications, the expansion of the village, the community Â